Fabrication of Nonwetting Flexible Free‐Standing MXene‐Carbon Fabric for Electromagnetic Shielding in S‐Band Region - Raagulan, Kanthasamy; Braveenth, Ramanaskanda; Jang, Hee Jung; Lee, Yun Seon; Yang, Cheol‐Min; Kim, Bo Mi; Moon, Jai Jung; Chai, Kyu Yun (Bulletin of the Korean Chemical Society, 2018)
MXene and nonwoven carbon fabric are good candidate for flexible, light‐weight electromagnetic interference (EMI) shielding fabric. The prepared composite was characterized using X‐ray diffraction, X‐ray photo electron spectroscopy, energy‐dispersive X‐ray spectroscopy, scanning electron microscope, mapping, and Raman spectroscopy. The 15 times coated composite displayed a contact angle of 123°, a wetting energy of −39.86 mN/m, a spreading coefficient of −112.66 mN/m, and 32.94 mN/m work of adhesion. The fabricated composites inhibited thermal degradation until 235 °C. The composite revealed an excellent electric conductivity of 8.5 S/cm with a sheet resistance of 6.5 Ω/sq. The composite showed a maximum EMI shielding of 43.2 dB at 2.3 GHz with 8534.7 dB cm2/g. The composite displays better outlook application areas such as aviation, portable electronics, radars, aerospace, and military.